Pengaruh Komitmen Organisasi dan Lingkungan Kerja terhadap Kinerja PT Bukit Bara Alam Kabupaten Lahat - Rahmat Rafli; Zaleha Tri Handayani; Efrina Masdaini (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2023)
This study aims to determine the effect of organizational commitment and work environment on employee performance. The population in this study were 42 people with a sample of 38 people using simple random sampling technique. The data required are primary data and secondary data. The data collection method in this study was a questionnaire. The data analysis technique used is multiple linear regression with the hypothesis of the f test, t test, and the coefficient of determination. The results of multiple linear regression test Y = 0.365 + 0.557X1 + 0.421X2 show that there is a positive influence between organizational commitment and work environment on employee performance. The results of the hypothesis test Fcount value (112.338) > Ftable (3.27), with a sig level. F 0.000 <0.05 indicates that there is a significant influence between organizational commitment and work environment simultaneously affecting employee performance. The results of the hypothesis test tcount for organizational commitment of 4.610> t table 2.030 with a sig. t level of 0.000 < 0.05 and the tcount for the work environment of 3.163> t table 2.030 with a sig. t level of 0.003 < 0.05 indicate that there is an influence between organizational commitment and work environment partially affect employee performance. The coefficient of determination shows that organizational commitment and work environment contribute 85.8% to changes in employee performance.